2011
DOI: 10.1186/1472-6963-11-246
|View full text |Cite
|
Sign up to set email alerts
|

Filmless versus film-based systems in radiographic examination costs: an activity-based costing method

Abstract: BackgroundSince the shift from a radiographic film-based system to that of a filmless system, the change in radiographic examination costs and costs structure have been undetermined. The activity-based costing (ABC) method measures the cost and performance of activities, resources, and cost objects. The purpose of this study is to identify the cost structure of a radiographic examination comparing a filmless system to that of a film-based system using the ABC method.MethodsWe calculated the costs of radiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
6
0
3
Order By: Relevance
“…In the present BIA, however, we observed that the low-cost PACS is advantageous for small-scale services because it has a low impact on the budget by avoiding costs with hardware and software and having low maintenance costs. Another recent study [17] concluded that PACS, when compared with the screen/film system, has much lower costs, offering a higher effectiveness for the health system and the patients. A study from the 1990 s [18] showed a reduction in hospitalization costs associated with faster and more precise diagnostics owing to the use of PACS.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the present BIA, however, we observed that the low-cost PACS is advantageous for small-scale services because it has a low impact on the budget by avoiding costs with hardware and software and having low maintenance costs. Another recent study [17] concluded that PACS, when compared with the screen/film system, has much lower costs, offering a higher effectiveness for the health system and the patients. A study from the 1990 s [18] showed a reduction in hospitalization costs associated with faster and more precise diagnostics owing to the use of PACS.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, frequent evaluations are required, always taking into account the characteristics of the health service, the user profiles, and the level of expertise of the medical staff. It is important to point out that with the current situation, the implementation of the PACS apart from generating lower costs and BI in any scenario would also result in a productivity increase of up to 200% to 300% [16][17][18]. This would obviously require the preparation of the entire team in terms, for example, of greater agility in the generation of reports and an entire infrastructure for a demand higher than previously planned, considering the associated increase in demand.…”
Section: Discussionmentioning
confidence: 98%
“…To decrease imaging costs, it is recommended that hospitals run a film-less system in their radiology departments. This allows better identification of costs and the reduction of the cost of services in this department ( 14 ). Some of the study’s limitations were diversity of radiology services, poor cooperation of personnel in delivering information about their activities in the departments, and also collecting and agreement on activity drivers.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in another study, there was a significant difference between the average cost of medical services and their tariffs that caused losses in the departments that were studied ( 13 ). Muto concluded in his study that film-less systems were more effective than film-based systems in delivering services to patients in radiology departments ( 14 ). Nisenbaum et al calculated the cost of C.T.…”
Section: Introductionmentioning
confidence: 99%
“…Tabela 2 -Distribuição de custos totais considerando-se 5000 exames e efetividade da realização, visualização/ interpretação de mamografias digitais na faixa etária dos 50 aos 69 anos, comparando-se o sistema PACS com uso de monitor específico e o sistema tela/filme. mamografia através de monitores de alta resolução e específicos para esse fim, proporciona o processamento de imagens, possibilitando sua aproximação e janelamento, dentre outros recursos que trazem melhora na acurácia de interpretação do exame [30,31]. Esses recursos alcançaram melhores resultados em mulheres abaixo dos 50 anos de idade [16,17,24], pois, segundo os autores mulheres mais jovens, na pré-menopausa ou no período perimenopausal apresentam tecido mamário e heterogêneo mais denso, aspectos que dificultam a visualização/interpretação de imagens mamográficas em filmes.…”
Section: Discussionunclassified